Mammalian Transcription Factor ATF6 Is Synthesized as a Transmembrane Protein and Activated by Proteolysis in Response to Endoplasmic Reticulum Stress - Haze, Kyosuke (The American Society for Cell Biology, 1999)
The unfolded protein response (UPR) controls the levels of molecular chaperones and enzymes involved in protein folding in the endoplasmic reticulum (ER). We recently isolated ATF6 as a candidate for mammalian UPR-specific transcription factor. We report here that ATF6 constitutively expressed as a 90-kDa protein (p90ATF6) is directly converted to a 50-kDa protein (p50ATF6) in ER-stressed cells. Furthermore, we showed that the most important consequence of this conversion was altered subcellular localization; p90ATF6 is embedded in the ER, whereas p50ATF6 is a nuclear protein. p90ATF6 is a type II transmembrane glycoprotein with a hydrophobic stretch in the middle of the molecule. Thus, the N-terminal half containing a basic leucine zipper motif is oriented facing the cytoplasm. Full-length ATF6 as well as its C-terminal deletion mutant carrying the transmembrane domain is localized in the ER when transfected. In contrast, mutant ATF6 representing the cytoplasmic region translocates into the nucleus and activates transcription of the endogenous GRP78/BiP gene. We propose that ER stress-induced proteolysis of membrane-bound p90ATF6 releases soluble p50ATF6, leading to induced transcription in the nucleus. Unlike yeast UPR, mammalian UPR appears to use a system similar to that reported for cholesterol homeostasis.